Effect of caffeine on sprint cycling in experienced cyclists - Anderson, D. E.; LeGrand, S. E.; McCart, R. D. (The Journal of Strength and Conditioning Research, 2018)
Research regarding the ergogenic effects of caffeine (CAF) in anaerobic activity remains inconclusive. However, some researchers have found significant improvements in anaerobic performance when testing specifically trained athletes. A double-blind, placebo-controlled, counterbalanced, cross-over design was implemented to assess the impact of CAF on a 30-second Wingate Anaerobic Test (WAnT) in experienced cyclists. Nine experienced cyclists volunteered to participate in this study (men, n = 7 and women, n = 2). The subjects completed 2 separate experimental trials consisting of a 30-second WAnT at a resistance of 9% body mass. In a random order, 1 hour before each WAnT, subjects ingested either a CAF (~280 mg) or placebo (PLAC) coffee. For each trial, heart rate (HR) and blood lactate (BL) values were recorded at rest, pre-WAnT, post-WAnT, and 5 minutes post-WAnT. After each trial, the subjects recorded their perception of which treatment they received. Heart rate and BL responses were not significantly different between the CAF and PLAC conditions. The ingestion of CAF did not significantly improve peak anaerobic power, mean anaerobic power, nor fatigue index. In at least 1 of the 2 trials, 44% of the subjects incorrectly guessed which substance they had ingested. The findings of this study do not show a significant correlation between CAF ingestion and improved anaerobic performance in experienced cyclists. However, performance enhancements may depend on varying individual responses to CAF. Athletes who are positive CAF responders may consider using coffee before competition to improve anaerobic performance.